ANALISIS KETAHANAN KELUARGA LONG DISTANCE MARRIAGE DALAM PERSPEKTIF HUKUM ISLAM; STUDI PADA KARYAWAN CV SINAR BARU SIDOARJO - Auliya Firdaus; Nashrun Jauhari; Purwo Widodo (Fakultas Syariah IAI Al-Khoziny Buduran Sidoarjo, 2026)
A harmonious atmosphere in a family is certainly everyone's dream, while couples who experience long distance marriage do not have enough time to communicate with each other so that they are at risk of having less strong family resilience and lack of harmony in the family. This study aims to determine the resilience of long distance marriage families among CV Sinar Baru employees in Sidoarjo Regency in 2024, so that it can be seen whether the resilience of long distance marriage families is able to maintain the family or not. This research method uses descriptive qualitative, namely research that provides a picture in the field of several situations and conditions in the research field. The primary data used is data collection with observation instruments, interviews, field notes and the use of documents.. Based on the results of the study, it was concluded that CV Sinar Baru employees have strong family resilience, because there is no divorce and they have their own way to maintain their family resilience and they apply the character of family resilience in the concept of Islamic family including: first, There is a strong bond of agreement. Second, There is a guarantee of safety and physical health of the family. Third, There is a guarantee of economic needs. Fourth, There is a bond of instinctive love and affection. Fifth, There is a bond of natural unity. and Sixth, There is family interaction in a moral manner and according to the review of PERMEN PPPA No. 06 of 2013 concerning the Implementation of Family Development.